ANALISIS JARINGAN VSAT DENGAN METODE QUALITY OF SERVICE (STUDI KASUS KABUPATEN MUARA ENIM) - Irwansyah, Irwansyah; Ependi, Usman (JURNAL ILMIAH MATRIK, 2012)
VSAT networks are used in several districts in Indonesia is a program of the Minister of Communications and Information Technology. Program is a form of Internet network equipment providers kesetiap districts spread almost all over Indonesia. Enim Muara district is one of the counties that have organized the rural Internet access service. Referring to the importance of quality network service and not execution of definitive measurements that can be used to measure how much of a good quality service is the central issue in this study is the "Analysis of performance-based rural Internet centers in the district of Muara Enim VSAT". Tools used in this study Biznet Axence NetTools and the Speed Meter. While the methods used action research model with QOS monitoring system, which consists of QOS monitoring, monitor,anddthehmonitoredhobjects Keywords: PLIK, QUALITY OF SERVICE, VSAT